2015
DOI: 10.1136/bmjopen-2014-006779
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postneonatal, infant, child and under-5 mortality in Nigeria: a pooled cross-sectional analysis

Abstract: ObjectivesTo identify common factors associated with post-neonatal, infant, child and under-5 mortality in Nigeria.Design, setting and participantsA cross-sectional data of three Nigeria Demographic and Health Surveys (NDHS) for the years 2003, 2008 and 2013 were used. A multistage, stratified, cluster random sampling method was used to gather information on 63 844 singleton live-born infants of the most recent birth of a mother within a 5-year period before each survey was examined using cox regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
154
6
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(212 citation statements)
references
References 50 publications
50
154
6
2
Order By: Relevance
“…This finding is consistent with previous studies. [12,13,14,15] Children from households with parity between 3-4 children and 5 or more children respectively had a significantly lower risk of child mortality. This is consistent with the finding of similar study conducted in Tanzania.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous studies. [12,13,14,15] Children from households with parity between 3-4 children and 5 or more children respectively had a significantly lower risk of child mortality. This is consistent with the finding of similar study conducted in Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Numerous studies on the determinants of child mortality have been conducted in LMICs including Nigeria. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Findings of these studies showed…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The burns injury in the present reported case was a result of ignorance of the mother about the correct place to seek help from in management of rectal prolapse. Study note that the mother's social background was complex.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, scalds and burns may occur in children from the high-income countries, whereas most of the burns in children low and medium income countries(LMIC) are accidental or due to ignorance on the part of the care givers. [2][3][4] A peculiarity of burns in the LMIC is that they may be intentionally inflicted for treatment of some conditions as febrile convulsions. 5 Irrespective of whether the burns injury sustained was intentional or not, the patient who has sustained it needs treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Under-five mortality was defined as the probability of dying before completing the fifth birthday; this was used as the outcome variable. The explanatory variables that were selected were based on a number of prior studies [2,21,22,23]. The following explanatory variables were included in the study: maternal age, highest level of education of mother, place of residence, method of family planning, source of drinking water, assistance at delivery, duration of breast feeding and the preceding birth interval.…”
Section: Study Variablesmentioning
confidence: 99%